Doris Day Confidential: Hollywood, Sex and Stardom - McDonald, Tamar Jeffers (I.B. Tauris, 2019)
Doris Day was a major star during the 1950s and '60s. Today, forty years after her last film, the star (who was ninety in April 2012) is often still invoked as shorthand for a kind of sexuality now felt outmoded, being typecast as 'the forty year old virgin'. Close attention to the facts of Day's own life (three times married) challenges this assumption and the majority of her film roles also prove otherwise, with Day most frequently portraying a woman of maturely sexual desires. How did such pejorative labelling arise, and why has it stuck so tenaciously to Day, even now?This book addresses t
https://katalog.adlr.link/Record/0-1694750639